Development of an SPE- HPLC-DAD method for the experimental study of florfenicol and florfenicol amine in pig cerebrospinal fluid - Šandor, Ksenija; Andrišić, Miroslav; Žarković, Irena; Perak, Eleonora; Vujnović, Anja; Terzić, Svjetlana (2020)
A study of florfenicol (FF) and its metabo- lite florfenicol amine (FFA) in pig cerebrospinal fluid was conducted following repeated intramuscular administration of the original (reference) and a generic veterinary medicinal product (VMP) under the same experimental conditions (20 mg FF/kg body weight, 48-hour interval). Both VMPs are solutions for injection containing FF as an active substance in the concentration of 300 mg/mL and have been authorized in Croatia for use in cattle and pigs. In this study, clinically healthy pigs were randomly divided into three groups. The first group was treated with the reference VMP, the second with the generic VMP, while the third served as the control group. Animals were sacrificed at 216, 288 and 384 hours after the first drug administration. Cerebrospinal fluid samples were analysed by the optimized and validated high-performance liquid chromatography-diode array detector method (HPLC-DAD). The solid-phase extraction (SPE) technique was chosen for sample preparation. The HPLC-DAD method provides good linearity over the concentration range of 0.05 to 5.00 μg/mL for FF and FFA. Limits of detection were 0.0023 μg/mL for FF and 0.0100 μg/mL for FFA. Extraction recoveries of FF were from 86.6% to 111.8%, and of FFA from 91.7% to 98.8%. The SPE-HPLC-DAD method has been demonstrated to be a selective, sensitive and suitable analytical method for the determination of FF and FFA in cerebrospinal fluid. The present study was based on a preliminary study that quantified FF in pig plasma at 216 hours after the first application of reference or generic VMP. However, FF and FFA were not detected in any of the cerebrospinal fluid samples during the experimental period. According to the nature of biological fluids, the SPE-HPLC-DAD method can be suitable for further pharmacokinetic studies of FF in pig plasma and serum after intramuscular administration of VMPs.
Raspodjela florfenikola (FF) i njegovog metabolita florfenikol amina (FFA) u cerebrospinalnoj tekućini svinja istražena je nakon dvokratne primjene u mišić s 48-satnim razmakom originalnog i generičkog veterinarsko-medicinskog proizvoda (VMP) iste terapijske doze (20 mg FF/kg tjelesne mase) u istim uvjetima pokusa. Oba VMP-a imaju odobrenje za stavljanje u promet u Hrvatskoj te su po farmaceutskom obliku otopine za injekcije i sadržavaju 300 mg FF/mL. Pokus je proveden na klinički zdravim svinjama raspoređenim u dvije pokusne i jednu kontrolnu skupinu. Prvoj pokusnoj skupini životinja primijenjen je originalni, drugoj skupini generički lijek, dok je treća skupina bila kontrolna. Žrtvovanje životinja uslijedilo je nakon 216, 288 i 384 sata od prvog davanja VMP-a. Uzorci cerebrospinalne tekućine prikupljeni su u trenutku žrtvovanja i analizirani su optimiranom i validiranom tekućinskokromatografskom metodom uz detekciju UV-detektorom s nizom fotodioda (HPLC-DAD). Obrada uzoraka cerebrospinalne tekućine provedena je ekstrakcijom na čvrstoj fazi C18 (SPE). Primjenom SPE-HPLC- DAD metode ustvrđeno je da matrica ne utječe na linearnost FF i FFA u radnom području od 0,05 do 5,00 μg/mL te je postignuta granica detekcije od 0,0023 μg/mL za FF i od 0,0100 μg/mL za FFA. Vrijednosti analitičkih povrata kreću se od 86,6 % do 111,8 % za FF, odnosno od 91,7% do 98,8% za FFA. U ovom radu je dokazano da je SPE-HPLC-DAD metoda selektivna, osjetljiva i pouzdana analitička metoda za određivanje FF i FFA u cerebrospi- nalnoj tekućini. S obzirom na rezultate našeg preliminarnog istraživanja FF u plazmi svinja tretiranih originalnim, odnosno generičkim VMP-om, cilj ovog istraživanja bila je i usporedba distribucije FF u uzorcima plazme i cerebrospinalne tekućine svinja nakon 216. sata od primjene VMP-a. Međutim, u uzorcima cerebrospinalne tekućine svinja žrtvovanih u navedenom pokusnom razdoblju nisu detektirani ni FF ni FFA.
Bibliografija: 30 jed.
Summary ; Sažetak.
Keywords: Svinje -- Florfenikol -- Florfenikol amin -- Cerebrospinalna tekućina -- Veterinarsko-medicinski proizvodi